T Follicular Helper Cell Subsets and the Associated Cytokine IL-21 in the Pathogenesis and Therapy of Asthma - Gong, Fang; Zheng, Ting; Zhou, Pengcheng (Frontiers in Immunology, 2019)
For decades long, it has been considered that T helper 2 (TH2) cell predominantly regulates the pathogenic manifestation of allergic asthma, such as IgE-mediated sensitization, airway hyperresponsiveness and eosinophil infiltration. However, recent discoveries significantly shift our understandings of asthma from a simple TH2 cell-dependent disease to a heterogeneous disease regulated by multiple T cell subsets including T follicular helper (TFH) cell. TFH cell, a specialized cell population that provides help to B cell, has attracted intensive attention in the past decade because of its crucial role in regulating antibody response in a broad range of diseases. In particular, TFH cells are essential for the IgE antibody class-switching. In this review, we summarize recent progresses on TFH cell and its signature cytokine interleukin (IL)-21 in asthma from mouse studies and clinical reports. We further discuss future therapeutic strategies to treat asthma by targeting on TFH cell and IL-21.